Cytotoxic and genotoxic effects of oxime β-lapachone in human cancer cells: selectivity toward NCI-H460 and insights from molecular docking - Maria Francilene Souza Silva; Lara Polyana Silva Ramos; Fátima de Cássia Evangelista de Oliveira; Bruno Marques Soares; Daniel Pascoalino Pinheiro; Igor Frederico da Silveira Ramos; Rayran Walter Sousa; Victória Laysna dos Anjos Santos; Arlan de Assis Gonsalves; Paulo Michel Pinheiro Ferreira; Heurison Sousa e Silva; Cleônia Roberta de Melo Araújo; et al. (Human Cell, 2026)
β-Lapachone exhibits potent anticancer activity although its clinical application remains limited by toxicity and mechanisms of resistance. Therefore, structural modifications have been explored to improve its pharmacological profile. This study evaluated the cytotoxic, genotoxic, and toxicological effects of the oxime derivative β-lapachone oxime (Oxβ-Lp), together with its predicted pharmacokinetic properties and potential molecular interactions. Oxβ-Lp displayed cytotoxic activity against all tested cancer cell lines (NCI-H460, PC9, K562, and HepG2) after 72 h of exposure, with the greatest potency and selectivity observed in NCI-H460 non-small cell lung cancer cells (IC₅₀ = 1.88 µM; SI = 13.1). Mechanistic analyses demonstrated reduced cell viability, mitochondrial membrane depolarization, DNA damage, and induction of apoptosis, without significant cell cycle arrest. In Allium cepa , Oxβ-Lp did not alter the mitotic index or induce micronucleus formation but promoted chromosomal aberrations and DNA strand breaks. The Artemia salina assay indicated high acute toxicity (LC₅₀ = 16.80 µg/mL). Molecular docking suggested a potential interaction between Oxβ-Lp and NQO1, with binding energies comparable to those of dicoumarol and similar interaction patterns within the catalytic site. Overall, these findings demonstrate that Oxβ-Lp exhibits selective cytotoxicity against NCI-H460 cells and promotes apoptosis associated with mitochondrial dysfunction and DNA damage. Although the molecular mechanisms underlying its biological activity require further investigation, Oxβ-Lp represents a promising scaffold for developing novel anticancer agents.